Mixed meal ingestion diminishes glucose excursion in comparison with glucose ingestion via several adaptive mechanisms in people with and without type 2 diabetes. Issue 1 (23rd October 2015) - Alsalim, W.; Tura, A.; Pacini, G.; Omar, B.; Bizzotto, R.; Mari, A.; Ahrén, B.
Abstract : Aims: To study the integrative impact of macronutrients on postprandial glycaemia, β‐cell function, glucagon and incretin hormones in humans. Methods: Macronutrients were ingested alone (glucose 330 kcal, protein 110 kcal or fat 110 kcal) or together (550 kcal) by healthy subjects (n = 18) and by subjects with drug‐naïve type 2 diabetes (T2D; n = 18). β‐cell function and insulin clearance were estimated by modelling glucose, insulin and C‐peptide data. Secretion of glucose‐dependent insulinotropic polypeptide (GIP) and glucagon‐like peptide‐1 (GLP‐1) were measured, and paracetamol was administered to estimate gastric emptying. Results: In both groups, the mixed‐meal challenge diminished glucose excursion compared with glucose challenge alone, and insulin levels, but not C‐peptide levels, rose more than after the mixed meal than after glucose alone. β‐cell function was augmented, insulin clearance was reduced and glucagon levels were higher after the mixed meal compared with glucose alone. GLP‐1 and GIP levels increased after all challenges and GIP secretion was markedly higher after the mixed meal than after glucose alone. The appearance of paracetamol was delayed after the mixed‐meal challenge compared with glucose alone. Conclusions: Adding protein and fat macronutrients to glucose in a mixed meal diminished glucose excursion. This occurred in association with increased β‐cell function, reduced insulin clearance, delayed gastric emptying and augmented glucagon and GIP secretion. This suggests that the macronutrient composition regulates glycaemia through both islet and extra‐islet mechanisms in both healthy subjects and in subjects with T2D.